Nilai Tambah Bunga Krisan Potong dan Bibit Bunga Krisan di Usahatani MQ Florist Kabupaten Cianjur - Riska Riska; Ernah Ernah (Universitas Galuh, 2026)
Chrysanthemum (Chrysanthemum sp.) is one of Indonesia’s leading ornamental plants and is widely popular and highly demanded by consumers. One of the main production centers of cut chrysanthemum flowers is located in West Java Province, particularly in Cianjur Regency. One chrysanthemum farming enterprise in this area is MQ Florist, which produces two chrysanthemum products, namely chrysanthemum seedlings and cut chrysanthemum flowers. Chrysanthemum farming has promising prospects due to increasing consumer demand; however, it also involves relatively high risks and production costs. This study aims to analyze the value added and profitability of chrysanthemum seedling and cut chrysanthemum flower farming at MQ Florist. The research design is qualitative, employing a case study approach with descriptive analysis and value-added analysis using the Hayami method. The results show that the value added of chrysanthemum seedlings and cut chrysanthemum flowers amounts to IDR 956.60 per cutting with a percentage of 70.73% and IDR 4,757.50 per bundle with a percentage of 76.9%, respectively. Meanwhile, the production profit of chrysanthemum seedlings is IDR 927.44 per cutting with a percentage of 68.57%, and the profit of cut chrysanthemum flowers is IDR 4,748.25 per bundle with a percentage of 76.74%.